Effects of By-Products from Oil Palm in Total Mixed Ration (TMR) in Goat Feed for Nutrient Utilization, Volatile Fatty Acid and Blood Metabolize - ไกรพรม, เทียนทิพย์; จันทรัตน์, สิทธิศักดิ์ (Princess of Naradhiwas University Journal, 2018)
The research aimed to study effect of by-products from oil palm of total mixed ration (TMR) in goat feed for nutrient utilization, volatile fatty acid, and blood metabolite in goats. Five Thai Native x Anglo-Nubian 50% crossbred male goat, 1.1±0.02 years old with average body weight (BW) of 25±3 kg, were arranged in 5 x 5 Latin Square Design. The goat were fed with ad libitum of total mixed ration of rice straw 30% (RS 30%) (TMR1), total mixed ration of oil palm frond 30% and palm kernel cake 20% and palm oil sludge 30% (OPF 30% +PKC 20% + POS 30%) (TMR2), total mixed ration of oil palm frond 30% and palm kernel cake 40% (TMR OPF 30% +PKC 40%) (TMR3), total mixed ration of oil palm frond 30% and palm kernel cake 20% and palm oil sludge 20% (OPF 30% +PKC 20% + POS 20%) (TMR4) and total mixed ration of oil palm frond 30% and palm kernel cake 25% and palm oil sludge 25% (OPF 30% +PKC 20% + POS 20%) (TMR5). The results showed that dry matter intake and protein intake in the goat group fed TMR2 and TMR4 were significant higher than TMR1, TMR3 and TMR4 (P<0.05). The digestibility of dry matter in the group fed TMR2, TMR4 and TMR5 were significant higher than TMR1 and TMR3 (P<0.05). Moreover, the digestibility of crude protein in the group fed TMR2 and TMR4 were significant higher than TMR1, TMR3, and TMR5 (P<0.05). The highest nitrogen balance was in goat fed group TMR2. And the nitrogen balance was significantly different. The mean of acetic acid in rumen fluid in the group fed TMR1, TMR2, TMR4 and TMR5 were significantly higher than TMR3 (P<0.05). Furthermore, the mean of propionic acid in group fed TMR3 and TMR5 were significantly higher than TMR1, TMR2 and TMR4 (P<0.05). And the mean of butyric acid in the group fed TMR1 and TMR5 were significantly higher than TMR2, TMR3 and TMR4 (P<0.05). The pH ammonia nitrogen concentration in rumen fluid, pack cell volume, blood urea nitrogen, and blood glucose of all groups of the goats were also not significantly different (P>0.05). Thus, the by products from oil palm as a total mixed ration source, had no effect on feed intake, nutrient utilization, volatile fatty acid, and blood metabolite in goats.